Fruit Sellers in the Country, Trinidad, B.W.I. - (:unkn) unknown (AnCog Agency; Printed in Saxony, 2009)
Street vendors of East Indian origin, sell vegetables on the sidewalk. Postcard number c 27274.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Women merchants--Trinidad and Tobago; East Indians--Trinidad and Tobago; Street vendors--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Ethnic costume--Indian; Clothing and dress--Trinidad and Tobago; Architecture--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Street signs--Trinidad and Tobago; Street names--Trinidad and Tobago